Aktivitas Antikoagulan Ekstrak Daun Pucuk Merah (Syzygium myrtifolium Walp.) pada Mencit Putih (Mus musculus L.) - Lusi Indriani; Rahmawati, Noveri; Sartika Murni (LPPM, Universitas Muhammadiyah Riau, 2025)
Red shoot leaves are known to contain secondary metabolic compounds such as alkaloids, flavonoids, tannins, triterpenoids, steroids, saponins, and phenolic compounds. Flavonoids are known to have cardioprotective activity, including the ability to inhibit platelet aggregation. This study aims to determine the potential of red shoot leaf extract (Syzygium myrtifolium Walp.) as an anticoagulant. The method used is the determination of coagulation time, carried out on days 0, 3, and 6, following the initial wounding of the mice’s tails. The tail is wounded using a sterile lancet at a distance at 2 cm from the tip, and blood is subsequently absorbed using a capillary tube. Coagulation time is measured by observing the formation of fibrin threads on the broken sections of the capillary tube every 15 seconds. Coagulation time is the time required for the formation of the fibrin thread. The study results on day 6 showed that the 100 mg/KgBW dose group of red shoot leaf ethanol extract demonstrated an effect of increasing coagulation time equivalent to the 100 mg acetosal group. Meanwhile, the 125 mg/KgBW dose group of red shoot leaf ethanol extract showed a stronger effect than the 100 mg acetosal group.